Efficacy and safety of sequential therapy for primary osteoporosis with bone formation promoters followed by bone resorption inhibitors: a meta-analysis - Yuxin Liu; Xin Liu; Yuefeng Wu; Tao Luo (Journal of Orthopaedic Surgery and Research)
Abstract Objective Through this study we aimed to present the latest and most comprehensive pooled analysis, providing an updated evaluation of the efficacy and safety of sequential therapy for primary osteoporosis, using bone formation promoters followed by bone resorption inhibitors. Methods PubMed, the Cochrane Library, Web of Science, and Embase databases were retrieved to identify pertinent studies. Randomized controlled trials (RCTs) on the sequential therapy of primary osteoporosis with bone formation promoters followed by bone resorption inhibitors were included. Data from clinical studies that met the eligibility criteria were extracted, and quality assessment and meta-analysis were performed using RevMan v5.4 and Stata v15.0. Sensitivity and subgroup analyses were performed to find the source of heterogeneity and discover more findings. Results A total of 10 eligible articles involving 14,510 patients (7171 in the intervention group versus 7339 in the comparator group) were included for the evidence synthesis. The baseline characteristics of the two groups were similar. Pooled analysis showed that the intervention group (bone formation promoters followed by bone resorption inhibitors) increased BMD at the spine (SMD:1.64; 95% CI: 0.97, 2.31; P < 0.00001; I2 = 99%), femoral neck (SMD: 0.57; 95% CI: 0.16, 0.99; P = 0.007; I2 = 96%), and total hip (SMD: 0.82; 95% CI: 0.16, 1.48; P = 0.02; I2 = 97%) compared with the comparator group (monotherapy or combination therapy using two drugs)for postmenopausal osteoporosis patient; however, there was no statistically significant difference observed in the increase of BMD at the 1/3 distal radius comparing the intervention group and comparator group (SMD: -0.25; 95% CI: -1.49, 0.99; P = 0.069; I2 = 92%). The incidence of new fractures was reduced in the intervention group relative to the comparator group (RR: 0.60; 95% CI: 0.43, 0.82; P = 0.001; I2 = 75%). The incidence of adverse events differed statistically between the two groups (RR: 0.85; 95% CI: 0.76, 0.95; P = 0.004; I2 = 97%), but the difference in adverse event incidence was not statistically significant among subgroups within the intervention and comparator groups. The intervention group had a superiority of Clinical efficacy. Conclusion Among patients with primary osteoporosis, sequential therapy with bone formation promoters followed by bone resorption inhibitors substantially increased BMD at sites such as the spine, femoral neck, and total hip while concurrently mitigating fracture risks. However, benefits regarding BMD at the 1/3 distal radius and the incidence of adverse events have not yet been established. Study registration Registered on PROSPERO (ID: CRD42023437188).